2008
DOI: 10.1108/09604520810871865
|View full text |Cite
|
Sign up to set email alerts
|

Testing the role of service quality on the development of brand associations and brand loyalty

Abstract: Purpose -The study aims to: measure brand associations in the context of a fitness club, test the influence of brand associations on the development of brand loyalty, and investigate the role of service quality on the development of brand associations. Design/methodology/approach -A total of 165 members of a managed-owned fitness club, located in North Greece, participated in the study. They completed a 25-item questionnaire to measure brand associations, and a 25-item questionnaire to measure service quality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 23 publications
(66 reference statements)
9
75
0
5
Order By: Relevance
“…In the context of health clubs, Alexandris et al (2008) Moreover, the researchers' findings supported Alexandris et al's (2008) and the inclusion of exercise commitment as an experience-induced antecedent of brand equity.…”
Section: Measuring Fitness Brand Equitymentioning
confidence: 54%
See 3 more Smart Citations
“…In the context of health clubs, Alexandris et al (2008) Moreover, the researchers' findings supported Alexandris et al's (2008) and the inclusion of exercise commitment as an experience-induced antecedent of brand equity.…”
Section: Measuring Fitness Brand Equitymentioning
confidence: 54%
“…Nevertheless, we consider the apparent differences between the services provided by health clubs and those provided by spectator sport organizations (e.g., leagues, franchises). However, scholars have suggested that the way in which sport consumers generate brand perceptions may be similar to that of fitness consumers (i.e., Alexandris et al, 2008;Williams & Pedersen, 2012). In particular, these studies have employed spectator-based brand equity (SBBE) model (Ross, 2006) in a health club context.…”
Section: Sport Brand Equitymentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of number of university was linked to low level of services provided to students (Alexandris, et al, 2008). Several aspects of student life including academic aspects, social and financial support and simple care suffer difficulty in coping with the increasing number of students.…”
Section: Problem Of the Studymentioning
confidence: 99%